Plastic bronchitis: A case report. (2019) - Grizales, Clara L.; González, Lina M.; Castrillon, Maria A.; Sua, Luz F.; Lores, Juliana; Aguirre, Marisol; Fernández-Trujillo, Liliana
Abstract: Plastic bronchitis is a rare and underdiagnosed disease characterized by the formation and expectoration of bronchial casts of amorphous material, which can be potentially fatal. It is more frequent in pediatric population. Symptoms can range from chronic cough and dyspnea to respiratory failure depending on the area of the compromised airway. Casts are classified as type I when constituted by inflammatory cells and accompany diseases such as asthma and pneumonias; and type II when acellular and are associated with congenital heart diseases following procedures such as Fontan. We report the case of a male schoolchild with a history of complex congenital heart disease, treated with palliative surgery, evaluated in the emergency department for cough and respiratory distress. The mother referred expulsion of gelatinous material after coughing. During clinical evaluation, expulsion of bronchial casts was evidenced, suggesting a plastic bronchitis. He underwent a diagnostic and therapeutic bronchoscopy and received initial treatment with respiratory therapy, nebulized hypertonic saline solution, mucolytics, dornase alpha and nebulized heparin. The hospitalization revealed a stenosis of the right pulmonary artery, which was corrected with stent. The patient progressed satisfactorily with improvement of cough and expectoration. He was discharged with combined treatment, nebulized medications and those concerning his underlying disease.